Transplantacje ex mortuo aktem (nie)miłosierdzia - Ewa Smerecka (Studia Theologica Varsaviensia)
Christian Mercy is inseparably associated with acting for human good. One of the fields where such action is seen towards others and which is supported by Church and media is transplant therapy. However, are treatments of such type really in line with the respect for human dignity and can be regarded as an act of mercy? In order to answer the above questions it is a good  idea to investigate the procedures which accompany organ transplantations, particularly including ex mortuo transplantations and brain death diagnosis with its medical justification. It is also essential to dwell on the quality of life, useful death, persistent therapy and widely understood term of conscience which appears in relation between donor and recipient. All these aspects make one think deeply on the validity and the proper assessment of ex mortuo transplantation especially when it is concerned as an action being in line with Christian Mercy.